A Trust-Based Reputation System for Security in the Internet of Vehicles (IoV) - Nozha, Dhibi; Makhlouf, Amel Meddeb; Zerai, Faouzi (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
The Internet of Vehicles (IoV) integrates with different nodes, like for example connected vehicles, roadside units, etc. Due to communication exchange, they are exposed to various attacks on the network, which poses a security risk. Nevertheless, security is a major concern in IoV networks, especially during data transmission. To address this issue, our team suggest an innovative approach. reputation management schema in an IoV environment to detect attacks at an early stage based on vehicle and driver behavior along with network state. Our algorithm combines direct and indirect trust with various metrics like Packet Lost Rate (PLR), vehicle speed distance between neighbors, alert content, and link quality. These metrics are used to compute a reputation score to identify malicious nodes. Based on its reputation, vehicles communicate with only trusted nodes. After assessment, we see that our solution surpassed the others solution and has demonstrated superior effectiveness in detecting abnormal vehicles. Furthermore, the computed delay, equal to 4.7 ms, does not affect the network communications, which is interesting for the introduced safety features.